University students are exposed to entertainment TV programs and their verifications - Al-Shammari, Mohammed Shaker Mahmood (Al-Adab Journal, 2021)
The researcher discussed in this study the nature of university students' exposure to recreational programs and the gratifications that these programs can achieve for them, and the current research problem lies in how Iraqi university students are exposed to TV entertainment programs and the patterns of that exposure and the verifications obtained from it, and the importance of the research stems from the fact that it deals with an important quality And dangerous TV programs, which are entertainment programs that have received great popularity and high interest in the audience for their follow-up, especially from the current study category, and they are young people who are clearly interested in pursuing such programs as competitions Singing, variety, music, comedy movies, sports, The research aims to determine the most important drivers of exposure, the type of entertainment TV programs and the attention that Iraqi university students attach to entertainment programs. The research reached a set of conclusions, the most important of which are: -1- Most of the respondents prefer exposure to film and series programs as well as cultural programs in addition to entertainment programs, as well as exposure to satirical and lyrical programs, among other types of entertainment programs.2 - The motivation to fill the free time ranked first in the motives of the viewers watching the entertainment programs.3- The feeling of joy and happiness is on top of the rest of the gratifications achieved by entertainment programs on satellite channels.